2019
DOI: 10.17219/acem/112785
|View full text |Cite
|
Sign up to set email alerts
|

Down syndrome as a cause of abnormalities in the craniofacial region: A systematic literature review

Abstract: Down syndrome (DS) is the most often diagnosed chromosomal disorder in newborns. The incidence is 1:792 live births. The article describes the irregularities and characteristics found in trisomy 21, which greatly affect the functioning of the stomatognathic system. The most significant disorders include the following: false macroglossia, muscular hypotonia and gothic palate. These abnormalities affect articulation, breathing, food intake, and swallowing. We analyzed the morphological characteristics of the cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 10 publications
2
46
0
4
Order By: Relevance
“…Parafunctional behaviours may vary considerably and seem to be significant predictors for the onset of TMD 6 as they overload the joint and masticatory muscles 13 . Particularly in DS patients, parafunctional characteristics are thought to develop from the combination of craniofacial alterations with retarded psychosomatic development 4 . A Brazilian study reported that 77.5% of DS patients suffering from TMD had at least one parafunctional behaviour, with an overall prevalence rate of 1.65% 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parafunctional behaviours may vary considerably and seem to be significant predictors for the onset of TMD 6 as they overload the joint and masticatory muscles 13 . Particularly in DS patients, parafunctional characteristics are thought to develop from the combination of craniofacial alterations with retarded psychosomatic development 4 . A Brazilian study reported that 77.5% of DS patients suffering from TMD had at least one parafunctional behaviour, with an overall prevalence rate of 1.65% 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Down syndrome patients may develop oral conditions that directly affect their systemic and oral health as well as their ability to interact socially 3 . Together with a retarded psychosomatic development, these issues may trigger the development of parafunctions and dysfunctions in these patients 4 …”
Section: Introductionmentioning
confidence: 99%
“…EDA-containing FN isoforms (EDA+ FN) play roles in migration, differentiation, signaling, adult wound healing and overall tissue health, with contesting beliefs on its role in fetal development [26,28]. EDA+ FN has increased binding affinity for integrins α 4 β 1 , α 9 β 1 , possibly α 4 β 7 , and RGD-associated α 5 β 1 , which enhances cell motility, proliferation and transformation in osteoblasts and fibroblasts [26,29].…”
Section: Plasma Fn Versus Cellular Fnmentioning
confidence: 99%
“…EDA+ FN has increased binding affinity for integrins α 4 β 1 , α 9 β 1 , possibly α 4 β 7 , and RGD-associated α 5 β 1 , which enhances cell motility, proliferation and transformation in osteoblasts and fibroblasts [26,29]. EDA also associates with Tolllike receptor 4 (TLR4) to generate inflammatory responses in the innate immune system (amnion cells); increased metalloproteinase (MMP) activity, cyclooxygenase 2 (COX2) expression, and prostaglandin E2 expression via the NF-κB and ERK1/2 pathways; and cytokine activity through the p38 and MK-2 pathways [28]. Murine studies have shown differential expression of EDA+ FN across injuries, from the wound site through the surrounding muscle into the dermis [30].…”
Section: Plasma Fn Versus Cellular Fnmentioning
confidence: 99%
“…Common oral features in patients with DS include the delayed eruption of deciduous and permanent dentition, an open bite or crossbite, Class III malocclusion, hypodontia, microdontia, macroglossia, and reduced oral cavity providing oral breathing and salivary leak. DS individuals usually present with poor oral hygiene and periodontitis [ 5 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%